2015
DOI: 10.1063/1.4929834
|View full text |Cite
|
Sign up to set email alerts
|

Relative resolution: A hybrid formalism for fluid mixtures

Abstract: We show here that molecular resolution is inherently hybrid in terms of relative separation. While nearest neighbors are characterized by a fine-grained (geometrically detailed) model, other neighbors are characterized by a coarse-grained (isotropically simplified) model. We notably present an analytical expression for relating the two models via energy conservation. This hybrid framework is correspondingly capable of retrieving the structural and thermal behavior of various multi-component and multi-phase flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(80 citation statements)
references
References 20 publications
5
75
0
Order By: Relevance
“…Conversely, we developed an analytical parameterization between the FG and CG models, which is just based on energy conservation [1]. Unlike those other strategies [38,39], we were consequently able of correctly retrieving across state space, the structural and thermal behavior of several nonpolar mixtures [1]. Besides, we showed that our hybrid approach can be considered as a generalized extension of established theories for uniform liquids, which assume a mean field for interactions beyond a certain distance [40,41,42,43].…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Conversely, we developed an analytical parameterization between the FG and CG models, which is just based on energy conservation [1]. Unlike those other strategies [38,39], we were consequently able of correctly retrieving across state space, the structural and thermal behavior of several nonpolar mixtures [1]. Besides, we showed that our hybrid approach can be considered as a generalized extension of established theories for uniform liquids, which assume a mean field for interactions beyond a certain distance [40,41,42,43].…”
mentioning
confidence: 98%
“…Once the two models are analytically connected with each other via energy conservation, Relative Resolution can capture the structural and thermal behavior of (nonpolar) multi-component and multi-phase systems across state space. The current work is a natural continuation of our original communication [1]. Most importantly, we present the comprehensive mathematics of Relative Resolution, basically casting it as a multipole approximation at appropriate distances; the current set of equations importantly applies for all systems (e.g, polar molecules).…”
mentioning
confidence: 99%
See 3 more Smart Citations